Echocardiographic study of left ventricular structure and functions in patients with chronic liver disease and its correlation to disease severity - Rakesh Roshan; Praphull Deepankar; Umesh Prasad; Manoj Kumar Chaudhary (Asian Pacific Journal of Health Sciences, 2018)
Background: The concept of cirrhotic cardiomyopathy includes impaired cardiac contractility, decreased beta‑adrenergic receptor function, abnormal beta‑adrenergic post-receptor function, defective excitation‑contraction coupling, and cardiac conduction abnormalities. The aim of our study is to assess the cardiac dysfunctions in patients of cirrhosis of liver, irrespective of etiology, and establish correlation between severity of disease and incidence of cardiomyopathy. Methods: This was a cross‑sectional, observational study of patients with CLD without any known cardiac disease attending the medical outpatient and inward department of the tertiary care center. Selected patients after informed consent were investigated further along with M‑mode and Doppler echocardiographic studies to determine the cardiac structure and systolic and diastolic cardiac functions. Results: A total of 60 subjects were enrolled for the study. Maximum cases of this study, that is, 70% patients were in the age group of 40–60 years with the mean age of 51.82 ± 6.48 years and male: female ratio of 3.1:1. Prolongation of QTc is observed in 35% of the study group. Diastolic dysfunction (E/A <1.0) was found in 43.33% of cases, varying from 60% in model for end-stage liver disease Group III to 41.6% in Group I and 39.5% in Group II, showing a positive correlation between severity of cirrhosis and E/A ratio. The left ventricular mass index in subject showed its proportional increase in relation to degree of severity of cirrhosis. Conclusion: We demonstrated an increase in cardiac dysfunction, especially diastolic in the subjects and its significant associations with the severity of disease.